Disseminated Mycobacterium abscessus infection and native valve endocarditis - Rahi, Mandeep Singh (Respir Med Case Rep, 2021)
Mycobacterium abscessus is a rapidly growing mycobacterium. It rarely causes disseminated infection or endocarditis. A 55-year-old male with a history of hepatitis C, liver cirrhosis, intravenous drug use (last use was four years ago), and chronic back pain presented with a three-week history of a right calf nodular lesion. He did not have a fever, chills, rash, dyspnea, or cough. Laboratory data showed mild leukocytosis. Computed tomography of the chest revealed bilateral cavitating nodules. Skin biopsy, sputum, and blood cultures grew Mycobacterium abscessus. Therapy with meropenem, tigecycline, and amikacin was initiated. He was re-admitted with worsening lower back pain. A lumbar magnetic resonance imaging showed destructive changes of L4 and L5 vertebral bodies concerning for osteomyelitis. Blood culture and bone biopsy grew Mycobacterium abscessus again. An echocardiogram was performed due to persistent bacteremia, which revealed large vegetation on the tricuspid valve and small vegetation on the mitral valve. Therapy was changed to eight weeks of amikacin, with cefoxitin and imipenem for twelve months based on drug susceptibility. Treatment of disseminated Mycobacterium abscessus is challenging due to antibiotic resistance. Typically, multidrug therapy is warranted with at least three active drugs. In severe valvular endocarditis, valve replacement may be required.